Later Medieval Metaphysics: Ontology, Language, & Logic, edited by Charles Bolyard & Rondo Keele. - Ebbesen, Sten (Collegium Medievale, 2016)
This volume contains ten essays dealing with various aspects of medieval philosophy from the 13th and 14th centuries. It is dedicated to Paul Spade, professor emeritus of the University of Indiana, who richly deserves to be honoured for his long and faithful devotion to Dame Philosophia Mediævalis, but none of the articles takes its point of departure from one of his works.